Φιλήκοος καὶ φιλόμουσος. Sul ruolo del greco nell’educazione riformata a Danzica nel XVI seco - Peressin, Roberto (Collectanea Philologica, 2023)
The article presents the edition and commentary of an adhortatio to learn Greek addressed to the pupils of the Gymnasium Dantiscanum (Gdansk). The text was printed in 1571 as part of an anthology of Greek poems and prose composed by Humanist Michael Retell from Zittau (1530–1576). Retell was invited to Gdansk to organize the recently founded grammar school. Although a number of publications are now available on Retell, reconstructing his biography and commenting on his Latin works, however, there is still a lack of studies on his Greek output. They could help clarify the author’s use of ancient models, since his poems often have bilingual versions, and only the Latin ones have been studied. Moreover they could oﬀer more insight into the school and its scholars during its lesser-known early years of activity (1558–1580).